Do biochemical parameters and intradialytic symptoms affect post‐dialysis recovery time? A prospective, descriptive study. Issue 6 (8th February 2021) - Ozen, Nurten; Cepken, Tugba; Tosun, Betul
Abstract: The recovery time is defined as the time required to recover from the feelings of lassitude and fatigue. The daily activities of patients are affected by dialysis sessions, requiring significant time for patients to return to their routines. This situation implies a lower quality of life for HD patients. The aim of this study was to investigate the effects of biochemical parameters and intradialytic symptoms on post‐dialysis recovery time in maintenance HD patients. This study was conducted at a private dialysis center during June and August 2019. Data were collected using the "Descriptive Characteristics Form" and the "Dialysis Symptom Index." "STROBE check‐list" was used for the report of the study. The study was completed with 86 participants. The median post‐dialysis recovery time was 240 min (interquartile range, 120–360 min), and female patients exhibit significantly higher recovery time than male patients. The median BMI was statistically significantly higher in patients whose post‐dialysis recovery time was ≥240 min. Additional findings show that the post‐dialysis recovery time was shortened by 0.230 times for male patients, while intradialytic hypotension (IDH) prolonged the median post‐dialysis recovery time by 3.141 times. Factors underlying the IDH should be determined in order to eradicate the issue. The study was registered in ClinicalTrials.gov with the number NCT04274556.